The Witch's Guide to Cooking with Children - McGowan, Keith 1968-; Tanaka, Yoko (New York : Christy Ottaviano Books, 2009)
Young inventor Sol must regain his self-confidence if he and his younger sister are to escape the clutches of Hansel and Gretel's witch, to whom they have been led by their stepmother and the man they believe to be their father.
Keywords: Siblings -- Fiction; Witches -- Fiction; Self-confidence -- Fiction; Inventors -- Fiction; Characters and characteristics in literature -- Fiction; Germany -- Fiction